A Note on 'Distributive Terms, Truth, and The Port Royal Logic'. Issue 4 (1st October 2016) - Martin, John Neil
Abstract : A note correcting some technical terminology from linguistics found in 'Distributive Terms, Truth, and The Port Royal Logic ', this journal, Jan. 17, 2013, 133–54.